Daybreak - Mezzoforte; Polygram Records (Iceland : PolyGram Records, 1993)
Contains ten tracks of instrumental jazz-funk fusion genre.
CD 1 : Little Rock / (4:47) -- Down Town / (5:06) -- Daybreak / (5:05) -- After Hours / (4:33) -- Roller Coaster / (5:04) -- Cobra / (4:05) -- Jakarta Dream / (5:42) -- Everything You Want / (4:03) -- Journey's End -/ (6:32) - Silently / (4:16).
Koleksi Khas Wiramanja.
Fridrik Karlsson (guitar), Johann Asmundsson (bass), Kare Kolve (saxophone), Eythor Gunnarsson (keyboard), Gulli Briem (drums).
Title from disc label.
Keywords: Songs with instrumental ensemble; Songs (High voice) with instrumental ensemble -- Scores